2011
DOI: 10.1364/ao.50.001984
|View full text |Cite
|
Sign up to set email alerts
|

Material removal in magnetorheological finishing of optics

Abstract: A concept of material removal based on the principle of conservation of particles momentum in a binary suspension is applied to analyze material removal in magnetorheological finishing and magnetorheological jet processes widely used in precision optics fabrication. According to this concept, a load for surface indentation by abrasive particles is provided at their interaction near the wall with heavier basic (magnetic) particles, which fluctuate (due to collision) in the shear flow of concentrated suspension.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Recent studies [139][140][141][142] reported precisions in the order of nanometers in processing and surface roughnesses in the order of tenths of nanometers. The composite material used was based on an MR suspension along with abrasive microparticles such as silicon carbides, cerium oxide, etc., and the function of the material processed was examined.…”
Section: Ultrafine Polishingmentioning
confidence: 99%
“…Recent studies [139][140][141][142] reported precisions in the order of nanometers in processing and surface roughnesses in the order of tenths of nanometers. The composite material used was based on an MR suspension along with abrasive microparticles such as silicon carbides, cerium oxide, etc., and the function of the material processed was examined.…”
Section: Ultrafine Polishingmentioning
confidence: 99%
“…Magnetorheological finishing (MRF) is a novel optical surface processing method combining electromagnetics, fluid dynamics, analytical chemistry, processing technology, which was proposed by Kordonski in the 1990s [1]. Comparing to the traditional polishing, MRF abrasive is constantly delivered to the polishing zone, and polishing debris and heat are continuously removed.…”
Section: Introductionmentioning
confidence: 99%
“…These processes have radically different polishing mechanisms, including computer controlled polishing [6], ion beam figuring (IBF) [7], plasma-assisted chemical etching [8], magnetorheological finishing [9], magnetorheological jet polishing [10,11]. Many large aspheric even off-axis segments have been successfully fabricated using them [4,5].…”
Section: Introductionmentioning
confidence: 99%